If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-10=w/2-2
We move all terms to the left:
-10-(w/2-2)=0
We get rid of parentheses
-w/2+2-10=0
We multiply all the terms by the denominator
-w+2*2-10*2=0
We add all the numbers together, and all the variables
-1w-16=0
We move all terms containing w to the left, all other terms to the right
-w=16
w=16/-1
w=-16
| -6x+7(7x+13)=-124 | | 7x+22=5x+45 | | z2=3 | | y=5-1/2(-2) | | -2=x–66 | | -93=5x-3(-2x-13) | | 5(8+p)=35 | | 93=3+10r | | 17=r+15 | | 1/x=1.43 | | 0.002x=0.05=0.5 | | -3x+4(4x+10)=-64 | | 8x-3=-5x+6 | | f+9=-15 | | 6/9=4/b | | 27b+29-23b=9 | | x÷2-25=7 | | 5/4=4/a | | y=2/3(-6)-1 | | x+44+64=180 | | 32=(y-10) | | 84-12x=24 | | 3x+5x+8=18 | | 900=600(1.05)^x | | 2(2+x)=2(x+6) | | 7w+15=10w | | 2x+5=5x-85 | | -2(x+3)-3=-21 | | (12x)=(2x+5)=(17x-14) | | 2/5x-5=99 | | 15+8x+4=27 | | 12z+4=2(5z=8)-12 |